Country Partnership Framework for the Republic of Rwanda FY21-FY26 - World Bank; International Finance Corporation; Multilateral Investment Guarantee Agency (World Bank, Kigali, 2020)
Rwanda is widely celebrated for the remarkable social, political, and economic renaissance it has experienced in the years following the genocide against the Tutsi of 1994. However, Rwanda appears to have relatively higher poverty rates than African peers with similar income per capita, and its elasticity of poverty reduction to growth is low compared to high‐growing SSA peers. Poverty is concentrated in rural areas and among households with many children. Rwanda now faces challenges in fully translating its very strong growth into commensurate gains in poverty reduction and shared prosperity. This Country Partnership Framework (CPF) sets out the World Bank Group’s (WBG) plans for addressing the country’s development priorities as identified in the 2019 Systematic Country Diagnostic (SCD) and Rwanda’s National Strategy for Transformation (NST1) well as supporting Rwanda’s response to the Coronavirus (COVID‐19) pandemic to recover from the negative public health and socio‐economic impacts of the pandemic. The CPF takes into account Rwanda’s anti‐crisis response program as of mid‐May 2020, including the government’s emergency Economic Recovery Plan, although it will likely continue to evolve in coming months. It was agreed with the authorities that should the situation warrant considerable changes to the government’s strategy and its program with the WBG, the Performance and Learning Review (PLR) will be brought forward to accommodate such changes. The CPF spans two IDA cycles, IDA19 (July 2020 to June 2023) and IDA 20 (July 2023 to June 2026). Given the country’s preference for frontloading its IDA commitment, and a track record of making good use of additional IDA resources available, Rwanda will explore the use of additional resources from IDA windows.